2005
DOI: 10.1088/0022-3727/38/9/005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zr substitution on structures and ferroelectric properties of Bi3.25La0.75Ti3O12thin films

Abstract: Thin films of Bi3.25La0.75Ti3O12 (BLT) and B-site substituted BLT by Zr, i.e. Bi3.25La0.75Ti3−xZrxO12 (BLTZx, x = 0.20, 0.50, 0.75, 1.00 and 1.50) were fabricated on Pt/Ti/SiO2/Si substrates by pulsed laser deposition. Structures and electrical characteristics of the polycrystalline films were studied as functions of Zr composition. Structures were investigated by x-ray diffraction, scanning electron microscopy and Raman spectroscopy. It is revealed that the Zr substitution does not destroy the layered structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Recently, bismuth layered structure ferroelectrics (BLSFs) thin films were widely investigated due to their superior properties [1,2]. Among them, Bi 4 Ti 3 O 12 (BTO) is known to be a typical kind of layer-structured ferroelectrics.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, bismuth layered structure ferroelectrics (BLSFs) thin films were widely investigated due to their superior properties [1,2]. Among them, Bi 4 Ti 3 O 12 (BTO) is known to be a typical kind of layer-structured ferroelectrics.…”
Section: Introductionmentioning
confidence: 99%
“…Many papers that reported the substituted BTO in the B-site focused on the high valent cations such as V 5+ and W 6+ substituting for Ti 4+ [5,6] , but few papers reported the substitution of the equal valent cations such as Zr 4+ substituting for Ti 4+ . Zhang et al [7,8] showed that the Zr-doped bismuth titanate (Bi 4 Zr 0.5 Ti 2.5 O 12 , BZT) thin films had excellent ferroelectric properties. The properties of B-site Zr substituted BTO films are worth studying.…”
Section: Introductionmentioning
confidence: 99%
“…Undoped BTO shows a very larger spontaneous polarization along the a-axis (about 50 µC/cm 2 ), but BTO thin films have much lower of switching polarization and suffer from poor fatigue endurance [6]. Some researchers have suggested that proper ion substitution (at the A-site with Sm 3+ , Ca 2+ , Sr 2+ , La 3+ , Nd 3+ ion or B-site with V 5+ , Ta 5+ , Nb 5+ , W 5+ , Zr 4+ ion and both A-and B-sites) in the perovskite-type unit of BTO can effectively optimize the ferroelectric properties [7,8]. Takayuki et al reported that excellent ferroelectric propertied are obtained by co-substitution of La 3+ and V 5+ in BTO thin films using a metalorganic chemical vapor deposition [9].…”
Section: Introductionmentioning
confidence: 99%